(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
It is not a secret to any of us that today the process of globalization continues rapidly. In this sense, it is becoming global and spiritual in today’s world where various threats are increasing in the educational sphere the level of development of the dynamics of changes in our life, characteristic of it particular importance is attached to the implementation of laws and specific national characteristics related to this, moral threats, their rapid growth and finding a solution to them. In this article, the author describes in detail the process of globalization in modernizing Uzbekistan and the current moral threats and their main directions